Parricide in Thailand: Its Causes, Characteristics, and Factors - Manujantarat, Thitipun (Homicide studies, 2023)
To date, studies as to parricide have mostly pertained to Western contexts. This study is the first exploratory research to consider parricide in Thailand alongside its patterns, causes and factors within this specific socio-cultural context. In-depth interviews were employed with 21 male perpetrators of parricide serving sentences in three prisons in Thailand. These interviews found that the victims had abused and committed domestic violence against the perpetrator prior to the parricide. Furthermore, the act of parricide in each case derived from the anger of, and unplanned use of weapons (i.e., sticks, kitchen tools and farming tools) by, a sole perpetrator.